Internalization of Character Education Values in Shaping Elementary School Students' Religious Behavior - Alif Achadah; Wahidmurni Wahidmurni; Ahmad Fatah Yasin (STAI Hubbulwathan Duri, 2022)
Character is one of the characteristics or personalities inherent in a person. The state of the school, which is established by considering religious programs or activities, will be able to instill the religious character in students. The values of character education can be instilled with habituation activities so that they can become habits inherent in students. This study aims at analyzing the values of religious character education implemented in SD NU Kepanjen and SDI Global School Malang, interpreting the process of internalizing the values of religious character education, and determining the impact of applying the values of religious character education. This research employs a qualitative approach using case study as the type of study. The data collection techniques are interviews, observation, and documentation. The data were analyzed through data collection, data condensation, data presentation, and conclusion/verification. The data validity checking is performed through triangulation of data sources and triangulation of methods. The results of this study indicate that: (1) the concept of character education values to improve students' religious behavior are: (a) the concept of excellent academic character education and religious awareness. (b) the concept of academic excellence includes honesty, discipline, exemplary, honesty, tolerance, environmental awareness, and the concept of religious awareness including obedience, trust, and habituation; (2) the process of internalizing the values of character education to improve students' religious behavior through the habituation of performing dhuha prayer in congregation, performing dhuhur prayer in congregation, reading the Quran together, carrying out GJS (the activities of collecting waste), and conducting PHBI; (3) the impact of internalizing character education values on students' religious behavior by refining the concept of character education applied in schools as well as the habituation of activities containing academic excellence and religious awareness. These are the efforts to refine students' religious behavior so that they have high awareness in performing worship. Thus, the attitudes reflecting faith, piety, good behavior, social awareness, tolerance, honesty, and discipline can be created. The findings of this study are: the concept of excellent academic character education and religious awareness, habituation of character education activities, and awareness of performing worship